STRATEGI PENGEMBANGAN UMKM (USAHA MIKRO, KECIL, DAN MENENGAH) PADA ERA GLOBAL (Studi Kasus UD Pawon Kue di Kota Surabaya) - Prastiti Nur Islami; Made Siti Sundari; Firman Rosjadi Djoemadi (Perpustakaan Universitas Surabaya, 2018)
The growing global economic environment makes MSMEs must plan the right strategy to compete and grow. In this research, strategic plan is arranged through SWOT analysis by looking at internal environment that is strength and weakness and external environment that is Opportunity and Threat on company. The type of research used is descriptive with qualitative approach. The data in this research is obtained through observation, interview and documentation on the research case study that is UD. PawonKue. The data analysis method used is SWOT analysis with stages of arranging IFAS and EFAS matrix, merging IFAS and EFAS matrix, SWOT quadrant, and SWOT matrix. From the results of this study concluded that the appropriate strategy used in UD. PawonKue is an Aggressive Strategy or Growth Strategy. An Aggressive Strategy that can be applied in UD. PawonKue is optimizing business management, product development, and expanding market share.